Hubungan Pola Asuh Demokratis dengan Interaksi Sosial pada Remaja yang Menggunakan Smartphone di SMAN X Yogyakarta - Tri Jumiati; Muslimah Zahro Romas; Eny Rohyati (LPPM Universitas Proklamasi 45, 2021)
The purpose of this study was to determine the relationship between democratic parenting and social interaction in teenagers using smartphones in SMAN X Yogyakarta. This research method uses quantitative research methods with data collection using a scale that is the scale of social interaction and the scale of democratic parenting. The subjects in this study were adolescents between the ages of 15 and 18, totaling 107 students consisting of 4 classes. Analysis of the data used was the product moment correlation technique from Pearson. The results of the analysis show that the correlation coefficient rxy = 0.639 with p = 0.000 (p <0.01), which means there is a significant positive relationship between democratic parenting and social interaction in adolescents using smartphones. So that it can be concluded that democratic parenting affects social interactions in adolescents who use smartphones, the higher the level of democratic parenting parents, the higher the social interaction of teenagers who use smartphones, and vice versa. The effective contribution of democratic parenting with social interaction is 40.83%.